Indanthrone derived disordered graphitic carbon as promising insertion anode for sodium ion battery with long cycle life - Suryawanshi, Anil; Mhamane, Dattakumar; Nagane, Satyawan; Patil, Shankar; Aravindan, Vanchiappan; Ogale, Satishchandra; Srinivasan, Madhavi (Electrochimica Acta, 2014)
We report facile, one step synthesis of disordered graphitic carbon by high temperature (1000 degrees C) pyrolysis of indanthrone dye (ID). The pyrolysed carbon is disordered in nature and the same is clearly evidenced by various analytical techniques like X-ray diffraction, Raman spectroscopy and high resolution transmission electron microscopy. Na-insertion properties of such indanthrone dye derived disordered graphitic carbon (IDDGC) is evaluated in half-cell assembly (Na/IDDGC). The test cell delivered a reversible capacity of similar to 160 mAh g(-1) at current density of 25 mAg 1. In addition, excellent cycling profiles are noted for such IDDGC, which retains 67% of initial reversible capacity after 500 cycles. The present study clearly highlights the importance of disorder in the graphitic carbon for efficient Na-ion storage. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: anode; disordered carbon; indanthrone; Na-ion battery

Large scale synthesis of graphene quantum dots (GQDs) from waste biomass and their use as an efficient and selective photoluminescence on-off-on probe for Ag+ ions - Suryawanshi, Anil; Biswal, Mandakini; Mhamane, Dattakumar; Gokhale, Rohan; Patil, Shankar; Guin, Debanjan; Ogale, Satishchandra (Nanoscale, 2014)
Graphene quantum dots (GQDs) are synthesized from bio-waste and are further modified to produce amine-terminated GQDs (Am-GQDs) which have higher dispersibility and photoluminescence intensity than those of GQDs. A strong fluorescence quenching of Am-GQDs (switch-off) is observed for a number of metal ions, but only for the Ag+ ions is the original fluorescence regenerated (switch-on) upon addition of L-cysteine.

Surfactant free gram scale synthesis of mesoporous Ni(OH)(2)-r-GO nanocomposite for high rate pseudocapacitor application - Singh, Upendra; Banerjee, Abhik; Mhamane, Dattakumar; Suryawanshi, Anil; Upadhyay, Kush Kumar; Ogale, Satishchandra (RSC Advances, 2014)
We report a single-step surfactant-free gram scale hydrothermal synthesis of mesoporous Ni(OH)(2) nanoparticles and the Ni(OH)(2)-reduced graphene oxide (Ni(OH)(2)-r-GO) nanocomposite. Interesting morphological features are noted. These nanomaterials are examined and compared as cathode materials for pseudo-capacitor application through detailed characterizations. A high specific capacitance (C-s) of 1538 F g(-1) is observed for Ni(OH)(2)-r-GO even at a high current density of 40 A g(-1), whereas at the same current rate, bare Ni(OH)(2) shows C-s of only 936 F g(-1).

Triple nanocomposites of CoMn2O4, Co3O4 and reduced graphene oxide for oxidation of aromatic alcohols - Jha, Ajay; Mhamane, Dattakumar; Suryawanshi, Anil; Joshi, Sameer M.; Shaikh, Parvez; Biradar, Narayan S.; Ogale, Satishchandra; Rode, Chandrashekhar V. (Catalysis Science & Technology, 2014)
A composite of reduced graphene oxide (RGO) with oxides of manganese and cobalt together was prepared by a solvothermal method. During synthesis, both the reduction of graphene oxide as well as the growth of nanorod shaped CoMn2O4 and Co3O4 occurred simultaneously having a crystallite size of similar to 8 nm calculated from X-ray diffraction (XRD). The as-obtained triple nanocomposite material designated as RGO-MnCoO exhibited excellent activity for the liquid phase aerobic oxidation of aromatic alcohols under base-free conditions selectively giving the corresponding aldehydes (>85%). RGO loading was varied in the range of 1-10%, among which 1% RGO-MnCoO showed maximum catalytic activity enhancement of 24% as compared to the bare mixed oxide (MnCo-MO) for the oxidation of vanillyl alcohol. HR-TEM of RGO-MnCoO revealed that it was a composite material having uniform nanotubes of similar to 25 nm length and 6 nm diameter with a fringe pattern showing the (103) and (004) planes and lattice spaces of 0.26 nm and 0.22 nm, respectively, for the spinel CoMn2O4. The detailed studies on the morphology, size and composition of the as-prepared RGO-MnCoO nanocomposite by XRD, XPS, N-2-adsorption/desorption and O-2-TPD techniques were used to understand the role of RGO in the enhancement of catalytic activity for oxidation reaction.

Starch (Tapioca) to carbon dots: an efficient green approach to an on-off-on photoluminescence probe for fluoride ion sensing - Basu, Aniruddha; Suryawanshi, Anil; Kumawat, Begraj; Dandia, Anshu; Guin, Debanjan; Ogale, Satishchandra B. (Analyst, 2015)
Photoluminescent carbon dots of 4-5 nm size were prepared from starch (Tapioca Sago) through a solution method under mild conditions. The as-prepared carbon dots were used as photoluminescence probes for highly anion selective fluoride ion detection in aqueous solutions. A ready-to-use device is also demonstrated.

Graphene based nanocomposites for alloy (SnO2), and conversion (Fe3O4) type efficient anodes for Li-ion battery applications - Mhamane, Dattakumar; Aravindan, Vanchiappan; Taneja, Divya; Suryawanshi, Anil; Game, Onkar; Srinivasan, Madhavi; Ogale, Satishchandra B. (Composites Science and Technology, 2016)
Two types of trigol reduced one pot synthesized graphene (TRG) based nanocomposites (SnO2-TRG, and Fe3O4-TRG) are examined as potential anodes for Lithium ion battery (LIB) applications. The two specific systems represent different electrode reaction mechanisms, namely alloying, and conversion respectively. The high resolution transmission electron microscopy (HR-TEM) analysis confirms the uniform distribution of SnO2 (similar to 2 nm), and Fe3O4 (similar to 8 nm) particulates on ultrathin TRG nanosheets and highlights the importance of surfactant free synthesis. The SnO2-TRG, and Fe3O4-TRG exhibited the maximum reversible capacity of similar to 947, and similar to 1024 mA h g(-1), respectively. The results show that such graphene based composite materials can be effectively used as prospective anodes for LIB applications. (C) 2016 Elsevier Ltd. All rights reserved.

Highly stable laser-scribed flexible planar microsupercapacitor using mushroom derived carbon electrodes - Yadav, Poonam; Basu, Aniruddha; Suryawanshi, Anil; Game, Onkar S.; Ogale, Satishchandra (Advanced Materials Interfaces, 2016)
A report is presented on the fabrication of all solid-state interdigitated flexible microsupercapacitor using ultrafast and highly scalable laser scribing technique, using highly mesoporous carbon synthesized from biomass (mushroom) with hydrothermal preprocessing. The specific protocol used for carbon synthesis renders some unique property features to the material (surface area of 2604 m(2) g(-1) with hierarchical pore size distribution) in the context of supercapacitor electrode application. A polyvinyl alcohol (PVA)-H2SO4 gel electrolyte is used for electrochemical measurements. The microsupercapacitor shows high cyclic stability up to 15000 cycles. Moreover it shows nearly 90% stability after 1000 bending cycles at 60 degrees angle. It also retains its performance even under 120 degrees bending condition. This work represents a facile and fast technique for microscaled device fabrication that can be easily commercialized. Moreover, the mushroom-derived carbon used to make the electrodes holds great promise in context of the stability and flexibility of flexible supercapacitors.

Minute-made activated porous carbon from agro-waste for Li-ion battery anode using a low power microwave oven - Agarkar, Shruti; Yadav, Poonam; Fernandes, Rohan; Kothari, Dushyant; Suryawanshi, Anil; Ogale, Satishchandra (Electrochimica ACTA, 2016)
We demonstrate a very simple, cost-effective and superfast process for making Li-ion battery (LIB) anode grade carbon from agro-waste in the form of sugarcane bagasse using a low power microwave system. Activation of this bagasse derived carbon is carefully optimized by using various weight ratios of KOH to obtain the desired properties of functional carbon in terms of porosity and electrical conductivity. Low equivalent series resistance (ESR), low charge transfer resistance with good electrical conductivity, and optimum porosity for efficient ion diffusion make this carbon a good candidate for Li-ion battery anode material rendering a reversible capacity of 757 mAhg (1) at a current density of 100 mAg (1) and a good cycling performance at high current rates. (C) 2016 Elsevier Ltd. All rights reserved.

Red mud and li-ion batteries: a magnetic connection - Suryawanshi, Anil; Aravindan, Vanchiappan; Madhavi, Srinivasan; Ogale, Satishchandra B. (Chemsuschem, 2016)
Exceptional Li-ion battery performance is presented with the oxide component of the anode was extracted from red mud by simple magnetic separation and applied directly without any further processing. The extracted material has -Fe2O3 as the major phase with inter-dispersed phases of Ti, Al, and Si oxides. In a half-cell assembly, the phase displayed a reversible capacity (approximate to 697mAhg(-1)) with excellent stability upon cycling. Interestingly, the stability is rendered by the multiphase constitution of the material with the presence of other electrochemically inactive metal oxides, such as Al2O3, SiO2, and Fe2TiO4, which could accommodate the strain and facilitate release during the charge-discharge processes in the electrochemically active maghemite component. We fabricated the full-cell assembly with eco-friendly cathode LiMn2O4 by adjusting the mass loading. Prior to full-cell assembly, an electrochemical pre-lithiation was enforced to overcome the irreversible capacity loss obtained from the anode. The full-cell delivered a capacity of approximate to 100mAhg(-1) (based on cathode loading) with capacity retention of approximate to 61% after 2000cycles under ambient conditions.

Low-dimensional hybrid perovskites as high performance anodes for alkali-ion batteries - Tathavadekar, Mukta; Krishnamurthy, Shrreya; Banerjee, Aparna; Nagane, Satyawan; Gawli, Yogesh; Suryawanshi, Anil; Bhat, Suresh; Puthusseri, Dhanya; Mohite, Aditya D.; Ogale, Satishchandra (Journal of Materials Chemistry A, 2017)
State-of-the-art Li (or Na) ion batteries work by insertion/extraction of the alkali metal ions into a porous electrode material, where the overall capacity is strongly dependent on the accessibility of the host material interior to the ions. On the other hand, the performance stability depends on various factors governed by the specific constitution of the electrode. Here we show that molecularly engineered low-dimensional hybrid perovskites can work as excellent anode materials for alkali-ion batteries. We measure a high reversible capacity of 646 mA h g(-1) at 100 mA g(-1) with good stability tested up to 250 cycles for the benzidine mediated lead iodide based 1D system. An ex situ analysis of the electrodes reveals that the storage primarily occurs via the Li-x(or Na-x)Pb alloying/de-alloying process. We anticipate that these results open a new direction for the use of low-dimensional hybrid perovskites for energy storage applications.
Keywords: Generation; Inorganic-Organic Hybrid; Lead Iodide; lithiation-intramolecular electrophilic reaction; Na-Air Battery; Negative Electrodes; Organometal Halide perovskites; PB; Sequential Deposition; Solar-cells